Research on Tag-Based Narrative of Online Content and Associated Risks - Hu, Shengjing (Journal of Social Science and Humanities, 2025)
The production and dissemination of online content have always been important aspects of cyberspace governance. This paper selects tags as an entry point, analyzing how online content achieves the expression and prominence of its substance through three processes: production tagging, dissemination tagging, and reception tagging, utilizing tags as a narrative technique. Simultaneously, the research explores the risks associated with tag-based narratives during online content dissemination, including content distortion, group induction, and online conflict. It conducts a root cause analysis of these risks, aiming to provide new insights for cyberspace governance through the investigation of their origins. Meanwhile, this paper has discussed some constructive solutions to control the risks associated with the use of tags.